2017
DOI: 10.3892/ol.2017.6798
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arenobufagin on human pancreatic carcinoma cells

Abstract: Abstract. Pancreatic carcinoma (PC) is a deadly form of cancer with poor overall survival. Currently, chemotherapy such as gemcitabine and 5-fluorouracil (5-FU) are the most popular medications that can improve survival, but rapid drug-resistance makes the search for more effective drugs urgent. Upon looking for natural components to treat PC, it was found that arenobufagin, a cardiac glycosides-like compound, showed significant effects on the gemcitabine-resistant pancreatic carcinoma cell line Panc-1 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The results of gemcitabine treatment proved Panc-1 to be gemcitabine-resistant compared to the other cell lines, which has been described in the literature [27]. In accordance with this observation, Panc-1 cells have shown slight additive effects after combined therapy with gemcitabine.…”
Section: Discussionsupporting
confidence: 79%
“…The results of gemcitabine treatment proved Panc-1 to be gemcitabine-resistant compared to the other cell lines, which has been described in the literature [27]. In accordance with this observation, Panc-1 cells have shown slight additive effects after combined therapy with gemcitabine.…”
Section: Discussionsupporting
confidence: 79%
“…Arenobufagin (ARE, structure shown in Figure 1(a)), one of the effective constituents of toad venom, is a traditional Chinese medicine obtained from the skin and parotid venom glands of Bufo bufo gargarizans Cantor or Bufo melanostictus Schneider [11]. Anyway, a lot of studies have demonstrated its broadspectrum antitumor activities in cancers such as breast cancer, pancreatic carcinoma, and liver cancer [12][13][14]. We previously found that ARE can induce liver cancer cell apoptosis and autophagy through PI3K/Akt/mTOR signal routing [14]; induce cell cycle arrest and apoptosis in human cervical cancer HeLa cells [15]; have anticancer effect on human esophageal squamous cell carcinoma (its mechanism of exerting anticancer efficacy may be activation of cysteinecontaining aspartate proteolytic enzyme (caspase) by endogenous and exogenous pathways); promote apoptosis of esophageal cancer cells by enhancing caspase phosphorylation and activating p53 signaling [16]; promote apoptosis of human glioblastoma U-87 cells by inhibiting p38MAPK signaling pathway [17]; and inhibit epithelial-mesenchymal conversion by going down the β-catenin pathway, consequently repressing motility and invasiveness of prostate cancer PC3 cells [18].…”
Section: Introductionmentioning
confidence: 99%